Stannous fluoride protects gingival keratinocytes against infection and oxidative stress by Porphyromonas gingivalis outer membrane vesicles - Xie, Sancai; Tansky, Cheryl S.; Ashe, Julie; Gao, Fei; Ramji, Nivedita B.; Iberi, Vighter; Sun, Yiping; Ramji, Niranjan; Biesbrock, Aaron R. (Frontiers in Dental Medicine, 2024)
Objective To determine whether outer membrane vesicles (OMVs) of the periodontal pathogen Porphyromonas gingivalis (P. gingivalis) can infect gingival keratinocytes and stimulate reactive oxygen species (ROS) production, and to assess whether stannous fluoride (SnF2), stannous chloride (SnCl2) or 0.454% SnF2 toothpaste diluents can inhibit OMV infection. Methods OMVs were isolated from P. gingivalis culture and their morphology was characterized using scanning electron microscopy and transmission electron microscopy. OMVs were harvested, separated from parent bacteria, labeled with fluorescent probes, and added to proliferating gingival keratinocytes. Infection was monitored by measuring uptake of fluorescence. Free radicals and ROS were quantified by adding a separate CellROX fluorescent probe following 24 h incubation with OMVs, and automated fluorescence imaging was used to assess ROS generation rates. A dose response range of SnF2 and SnCl2 concentrations as well as 0.454% SnF2 toothpaste dilutions were added to OMVs to examine their potential to neutralize OMV infectivity and protect gingival keratinocytes from development of oxidative stress. The mechanism of SnF2 inhibition of OMV infection was studied by binding SnF2 with purified lipopolysaccharides (LPS) from the bacterial culture and examining the binding of stannous to LPS using mass spectrometry. Results Large numbers of OMVs were formed in P. gingivalis culture medium. They were purified along with isolating soluble LPS. Fluorescence imaging revealed that OMVs infected gingival keratinocytes and promoted oxidative stress in a dose-dependent manner. SnF2, SnCl2, and SnF2 toothpaste inhibited OMV infectivity (p < 0.05) and likewise protected gingival keratinocytes from oxidative stress (p < 0.05). Stannous precipitated LPS and OMVs from solution, forming insoluble aggregates easily isolated by centrifugation. Mass spectroscopic analysis revealed that stannous was bound to LPS in a one-to-one molecular equivalent ratio. Conclusion SnF2 not only kills bacteria, but also inhibits bacterial virulence factors, such as LPS and OMVs. SnF2, SnCl2 and stannous-containing toothpastes can precipitate OMVs and LPS to in principle protect gingival keratinocyte cells from infection leading to inflammation and oxidative stress.